Perbandingan Pengetahuan dan Minat Belajar PKn Jenjang SMA dan Perguruan Tinggi - Savitri Rahmadhanti; Shabrina Hafilah; Zelda Shakila Zivanka; Ayu Zaskia Dwi Nuhri Rafitri; Maulia Depriya Kembara (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
Civics Civics Education is an important subject in education to form awareness and understanding of the rights and obligations as good citizens. The purpose of this study is to increase knowledge and interest in learning Civics Education (PKn) among Students and College Students. The research method used is descriptive quantitative with a survey approach using a questionnaire. The results showed that there were significant differences in knowledge and interest between students and female students in learning Civics Education. Students tend to be more knowledgeable and more interested in civic learning than students. This could be due to factors such as higher level of education, wider life experience, and greater desire to learn civics. However, it should be noted that the results of this study should not be generalized to the entire student population. Other variables such as educational background, social environment, and personal factors can also influence knowledge and interest in learning civics. This article helps us better understand the differences in knowledge and interest in learning Civics between high school and university students. The implications of this study can be used to improve Civics teaching methods to be more effective and interesting for students.